PENGARUH FAKTOR PSIKOLOGIS TERHADAP KEPUTUSAN PEMILIHAN BIRO PERJALANAN UMROH PADA PT. NAMIRAH ANGKASA JAYATAMA (NAJA) TOUR & TRAVEL SEKAYU - Hendry Wijaya; Yeni Marsih; Rini Anggraini (Jurnal Manajemen Kompeten, 2018)
This study aims to determine the influence of psychological factors on the decision of the selection of travel agency umroh at PT. Namirah Angkasa Jayatama (NAJA) Tour & Travel Sekayu. Population used in this research is Population of this research is consumer who ever become jama'ah at NAJA Tour & Travel Sekayu. The population in this study is 200 Jama'ah. The sample in this research is 133 respondents. Sampling technique with purposive sampling technique. Based on the results of the research that has been done, the result shows that the psychological factor gives a low effect on the selection decision and there is a positive sign stating the unidirectional correlation, where the increase or decrease. The independent variable (X) will result in the increase or decrease in the dependent variable (Y).